THE CORRELATION BETWEEN MASS MEDIA ACCESS AND KNOWLEDGE ABOUT REPRODUCTIVE HEALTH IN ADOLESCENTS AT SMAN 1 DAWAN KLUNGKUNG - Erviana Puspita Dewi; Riza Kurnia Indriana; Ni Made Nurtini (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2019)
Background: Adolescence is a transition period of development from childhood to adulthood, between 10-24 years. The adolescence will experience changes during this period. The knowledge of health reproduction is very important for adolescence because the development of the adolescence is dynamic both biologically and psychologically as well as factors that influence knowledge of adolescence such as information received, parents, friends, closest people, mass media and frequent discussions so that the adolescence need to know about health reproduction in order to have right information about the process of reproduction and various factors that are around it. The purpose of this study was to analyze the correlation between mass media access and knowledge about reproductive health in adolescents at SMAN 1 Dawan Klungkung.Method: This study employed analytic study with cross sectional approach. There were 102 students of SMAN 1 Dawan recruited as sample of this study. The data were collected by using questionnaire and analyzed statistically by using Spearman Rank (rho) with p value < 0,05.Finding: The finding showed that 74 respondents (72.5%) had good level of knowledge. 95 respondents (93.1%) stated that access to mass media was reached. There is significant and positive correlation between mass media access and the level of knowledge about adolescent reproductive health (p value = 0.000) and (rs = 0.354).Suggestion: Health institutions and education are expected to provide more information about health reproduction in adolescents. For further research, the researchers are expected to add more research variable